FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI PUSKESMAS POMALAA KAB KOLAKA TAHUN 2017 - Herlina, Nina; Ekowati, Erik; Astuti, Dwi Puji; Ambariani, Ambariani; Yulia, Nita (UG Journal, 2020)
The perineum ruptuer is a tear that accurs in the perineal area during labor. From the data obtained at birth room Pomalaa Puskesmas 2016. The number of maternal mother as many as 876 mothers there are 270 mothers experiencing ruptu re of perineum of degree I and 510 mother have rupture perineum de gree II. Whreas in 2015 from January to October the number of maternal mother of 641 mother there are 168 mothers experiencing rupture of degree I and 388 mothers experience rupture of degre e II. The purpose of this study is to detemine the factors that effect the healing of perineal wound on postpartum mother ats Pomalaa Puskesmas Year 2016. Research Method : Analytic with cross sectional approach done on April 5 to April 28, 2017. The population in this study as many as 63 people, with Using total samplin g technique then got the sample amounted to 63 people, with Using total sampling technique then got the sample amounted to 63 respondents. Results: There is an inluence of knowledge with perineal wound healing by p- value 0,001, body mass index with perineal wound healing by p -value 0,005, personal hygiene with perineal wound healing by p- value 0,001, environmental influence with perineal wound healing by p - value 0,0001 and a socio-cultural influence with perineal wound healing at Pomalaa Public Health Center 2017, marked with p- value 0,005. Conclusion : There is influence between knowledge, body mass index, and personal hygiene environment, socio-culture towards healing of perineal wound healing at Pomalaa Health Center Year 2016.